(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Uzbekistan is the third producer of gas production in Eurasia, which began in 1953. However, it has not been able to become a major gas exporter due to it shigh domestic consumption. The gas industry has always been and remains the most important component of the country’s economy, and to a large extentе determines its current state and the pace of further development. This is explained by the fact that gas as a final product, as a semi-finished product for subsequent processing, and as a component of various technological processes is widely used in many spheres of human life. It is hardly possible today to imagine life without "blue fuel".